Design of analog modules using carbon nanotube field effect transistor (CNFET) - Lee, Lih Shiuan (2014)
Carbon Nanotube Field Effect Transistor (CNFET) with its unique electrical properties has the potential of becoming a future alternative technology. Currently, research on CNFET circuit design is at the initial stage and it is challenging compared to conventional CMOS. In CMOS design, the Id current equation is utilised to estimate the transistor size; whereas for CNFET, discussion on analog circuit design is limited. In addition, there are some CNFET parameters which are different from CMOS parameters need to be studied from design perspective. Therefore, a design technique has to be developed. In this project, challenges of CNFET design and differences with CMOS are identified. Various CNFET parameters are studied, which include diameter, channel length, pitch and number of tubes. Besides, the effects of CNFET parameters on circuit performance are explored and consequently the governing parameters are identified. In addition, the design approach is implemented in analog cells which include general purpose op amp. A considerable amount of HSPICE simulation using Stanford CNFET model has been performed to verify the proposed method. It is hope that the design approach developed in this project can be used as a guideline for circuit designer.